KARAKTERISASI MINERALISASI TEMBAGA-EMAS BERDASARKAN GEOKIMIA MULTIUNSUR DENGAN METODE K-MEANS DAN ANALISIS KOMPONEN UTAMA, TOGURACI, INDONESIA: CHARACTERIZATION OF COPPER-GOLD MINERALIZATION BASED ON MULTIELEMENT GEOCHEMISTRY WITH K-MEANS AND PRINCIPAL COMPONENT ANALYSIS METHODS, TOGURACI, INDONESIA - irwanda, Dharma; Mega F Rosana; Johanes Hutabarat (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
Multielement geochemical data processing with K-means and principal component analysis was carried out in the Toguraci, part of the Gosowong gold mine contract of work in North Halmahera Regency, North Maluku Province. Previous research has suggested that there is overprinting low sulphidation epithermal Au-Ag mineralization and Cu-Au porphyry. This research focused on 2 selected drill holes with a total of 540 samples that were analyzed for Au and 46 other geochemical elements. The purpose of this research is to determine the characteristics of the copper-gold mineralization, and its host rock with multielement geochemical analysis, in order to provide a guide for exploration activities. Multielement geochemical data processing with K-means produced 3 lithogeochemical clusters based on their immobile element composition, namely basalt and diorite which are the host rocks, and quartz vein. Principal component analysis shows consistent results for the 3 clusters, where the combination of PC1 and PC2 which cumulatively represented 46,32% of the variance, indicates high and low loading scores describing the association of immobile elements that separates basalt, diorite and quartz vein. Data simplification with 7 principal components (P1-PC7) representing 73,62% of the variance has produced 6 geological domains which have their respective geochemical characteristics, namely Quartz vein, Basalt-1, Basalt-2, Diorite-1, Diorite-2, and Diorite-3. Copper mineralization is found in Basalt-1 and Diorite-1 related to porphyry type that has characteristics of Mo-Cu-Re-Ge-Au elemental association. While gold mineralization is found in the Quartz vein domain related to low sulphidation epithermal type which is characterized by Ag-Sb-Te-Au-Tl-Bi-As-Pb-Se-In elemental association.